2022
DOI: 10.3390/ijms23147659
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Dependent Induction of Vasculogenic Mimicry in Human Triple-Negative Breast Cancer Cells Is Inhibited by Calcitriol and Curcumin

Abstract: In highly aggressive tumors, cancer cells may form channel-like structures through a process known as vasculogenic mimicry (VM). VM is generally associated with metastasis, mesenchymal phenotype, and treatment resistance. VM can be driven by antiangiogenic treatments and/or tumor microenvironment-derived factors, including those from the endothelium. Curcumin, a turmeric product, inhibits VM in some tumors, while calcitriol, the most active vitamin D metabolite, exerts potent antineoplastic effects. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Finally, knowing that PI3K–Akt is involved in VM activation [ 10 ], we pharmacologically inhibited this signaling pathway with LY294002 and found that VM was suppressed, further suggesting that the FGFR/PI3K–Akt axis was a main regulator of VM in our CCs. Other works have previously shown that FGFR or PI3K/Akt inhibition can impair both angiogenesis and VM in different types of cancer, and that the pan-FGFR inhibitor PD173074 impaired VM in cultured TNBC cells [ 38 , 71 , 76 , 77 , 78 ]; however, to our knowledge, this is the first report of VM inhibition in breast cancer by AZD4547 and LY294002, warranting future clinical studies.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Finally, knowing that PI3K–Akt is involved in VM activation [ 10 ], we pharmacologically inhibited this signaling pathway with LY294002 and found that VM was suppressed, further suggesting that the FGFR/PI3K–Akt axis was a main regulator of VM in our CCs. Other works have previously shown that FGFR or PI3K/Akt inhibition can impair both angiogenesis and VM in different types of cancer, and that the pan-FGFR inhibitor PD173074 impaired VM in cultured TNBC cells [ 38 , 71 , 76 , 77 , 78 ]; however, to our knowledge, this is the first report of VM inhibition in breast cancer by AZD4547 and LY294002, warranting future clinical studies.…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we and others have shown the paracrine contribution of ECs in tumor cell behavior, including TNBC VM formation [ 10 , 12 , 25 , 26 ]. In this study, our aim was to gain further insight into the contribution of cellular components of the tumor microenvironment in TNBC VM induction, focusing on identifying the participation of ECs and SCs in this process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the study of biomimetic mechanisms and associated inhibitors in OC remains a difficult research area. Certain anti-angiogenic mimetic drugs that have been applied to other tumors, including flavonoids ( 97 ), curcumin ( 98 ), doxycycline ( 20 ), thalidomide ( 60 ), and so on, need to be tested for their pharmaco-toxicological and pharmacokinetic properties before they can be formally applied in a clinical setting; therefore, there remains a long way to go before they can be applied for the treatment of OC angiogenic mimicry ( 99 ). Thus, there remains a long way to go before these agents can be used in therapeutic strategies for the treatment of OC angiogenic mimicry.…”
Section: Clinical Applicationsmentioning
confidence: 99%